Penerapan Media Animasi Dampaknya Terhadap Prestasi Belajar Ditinjau Dari Faktor Motivasi Belajar - Peri Ramdani; Muhammad Aditya Firdaus; Rinda Fauzian (Jurnal Ilmiah Wahana Pendidikan, 2021)
Finding problems at MTs. As-Solehhiyah is that there are still some students who are still not focused, feel bored, lack of enthusiasm in learning so that some of the students' values ​​are under the KKM. The purpose of this study was to determine the application of animation media to learning achievement of akidah akhlak, to know the application of motivation to learning achievement of akidah akhlak, and to know the application of animation media and motivation simultaneously to learning achievement of akidah akhlak. The approach taken in this study is a quantitative approach. The method used is the quasy experimental method. The population in this study was 30 students in each class. Data collection techniques were carried out through observation, questionnaires, and tests. The data analysis technique used in this study was the two-way Vactorial Analysis (ANAVA) technique. The results showed that the application of animation media can increase learning achievement by 12,656. Meanwhile, learning motivation can increase learning achievement by 66, 219. The application of animation media and learning motivation together can increase learning achievement by 3.508.